Main strategies for conceptualization of musical meaning - Makovetskaya, Maria Vladimirovna; Seliverstova, Nina Andreevna (Философская мысль, 2022)
The object of this research is music as a semantic process. The subject is problematization of the concept of meaning in music. The goal lies in outlining the main strategies for conceptualization of the musical meaning within the framework of the history of music-aesthetic teachings. The authors pursue the following tasks: conduct critical analysis of the basic music-aesthetic concepts, explore their metaphysical origins and ideological prerequisites, determine the conceptual boundaries of the concept of musical language. The acquire results lie in determination of the fundamental strategies for rationalization of music: music as mathematics, and music as language. Within the framework of these strategies, analysis is conducted on various concepts of the meaning in music and their metaphysical prerequisites. Among these concepts are musical ethos, world harmony, music affects, musical expression, and semiotics of music. The author clarifies the concept of music as language from the perspective of a range of discursive attitudes: musical language as a natural language of feelings (theory of musical expression), and musical language as a semiotic system. The scientific novelty of consists in application of the new approach towards reconsideration of the basic music-aesthetic concepts from the standpoint of the development of autonomization of the musical meaning. The research results justify drawing a clear boundary between the scientific and nonscientific discursive use of such common comparisons as "music as language" and "music as mathematics". The conclusion is made the solution to problem of the specificity of formation and functionality of the autonomous musical meaning requires going beyond the narrow field of consideration of music as a semantic process towards the holistic experience of aesthetic perception.